Challenges and Strategies of Teachers in Teaching English to Hearing-Impaired Students: An Inclusive Education Perspective - Maemuna Muhayyang; Andi Sukri Syamsuri; Herman Tahir; Syamsiarna Nappu; Andry Hasryan; Annisa Nur Hidayah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Teaching English to hearing-impaired students poses a pedagogical challenge for teachers due to the dominant auditory learning orientation. Thus, this research aims to study the challenges faced by teacher when teaching English to hearing-impaired students at SLB Negeri 1 Makassar, and the strategies used to address these issues from the perspective of inclusive education. The objective of this research is achieved through the application of a qualitative approach designed as a case study. A teacher was selected purposively as the research subject, and her teaching data was collected thru classroom observations, interviews, and documentation. The research findings identified five challenges faced by the teacher, namely communication, student differences in ability, a lack of learning resources, student distractions, and the students' limited vocabulary. To address these issues, teacher used adaptive approaches, that is visual teaching materials, in-person instruction, sign language, mobile-phones as learning aids, and intensive material repetition. These strategies are examples of inclusive pedagogical practices that emphasize adaptation, responsiveness, and flexibility in learning for hearing-impaired students. This research concludes that the pedagogical skills and teaching adaptations of teachers are important components that enable deaf students to learn English effectively in the classroom.